Validitas Lembar Kerja Berbasis Problem Based Learning (PBL) untuk Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik pada Bahan Kajian Energi Terbarukan - Wulanndari, Indah (Universitas Negeri Surabaya, 2023)
This study aims to analyze the results of the validity of Problem Based Learning (PBL) based worksheets to improve students' creative thinking skills on renewable energy study materials. This research product development method is an R&D method with the ADDIE development model. In this study using 3 stages, namely the Analyze stage where the activities carried out are problem analysis, curriculum analysis, and needs analysis. The Design stage where researchers design worksheets to be developed. At the Development stage, researchers conducted validation. The validity of the worksheet was assessed from 2 aspects of validity, namely content validity and construct validity. The analysis technique is calculated from the validity results assessed by 3 validators of Unesa Physics lecturers. The advantages of the worksheets developed are the novelty of PBL-based teaching materials, containing contextual problems, and training students' creative thinking skills. The weakness of this worksheet is that the worksheet cannot be accessed digitally. The results showed the average percentage of content and construct validity aspects were 94.44% and 91.67%, respectively. The overall average percentage of the worksheet is 93.05%. Based on the average percentage results, the worksheets are classified in the very valid category seen from the score interpretation from Sudijono in Oktafiana (2015). So it can be concluded that the PBL-based worksheets are very feasible to use for learning.